Paediatric travel medicine: vaccines and medications. (20th May 2013) - Starr, Mike
<x xml:space="preserve">Abstract</x> The paediatric aspects of travel medicine can be complex, and individual advice is often required. Nonetheless, children are much more likely to acquire common infections than exotic tropical diseases whilst travelling. Important exceptions are malaria and tuberculosis, which are more frequent and severe in children. Overall, travellers' diarrhoea is the most common illness affecting travellers. This review discusses vaccines and medications that may be indicated for children who are travelling overseas. It focuses on immunizations that are given as part of the routine schedule, as well as those that are more specific to travel. Malaria and travellers' diarrhoea are also discussed.